Influence of hot air temperatures on drying kinetics of whole persimmon - Cervera-Chiner, Lourdes; Vilhena, Nariane Q.; Gil, Rebeca; Moreno, Ana; Moraga, Gemma; Salvador, Alejandra (2024)
Persimmon (Diospyros kaki) has become one of the most important crops in Mediterranean area of Spain in last years. The production is based in ‘Rojo Brillante’, an astringent cultivar that requires a post-harvest treatment of deastringency before commercialization. The high volume of production, the short harvesting season and the high quality requirements of the market have led to an increase in post-harvest losses in recent years, which can reach up to 16-20% of production. Therefore, the development of value-added by-products is one of the challenges facing the persimmon sector. Recent studies show that the technique of natural drying of whole fruit, widely used in Asian countries, could be a good strategy to valorize the surplus of ‘Rojo Brillante’. However, the optimization of the drying process is necessary. In this study three different drying conditions were studied with the aim to determine the optimal condition to obtain an acceptable product for consumers and industrially profitable. Peeled persimmon fruit were subjected to forced air drying conditions at 35ºC, 40ºC or 45ºC. The target product must have a water content (Xw) of 30% and water activity (aw) of 0,7 approximately. For this, drying curves, physicochemical characterization of the three products were made. The results showed that drying at 45ºC reached that target parameters at the 6th day, while when the drying process was carried out at 40ºC or 35ºC, the same humidity was reached on the 8th and 12th day, respectively. During drying, changes in texture were observed, with the percentage of deformation increasing until the third day and stabilizing thereafter. However, the desired texture was achieved by the product obtained at 35ºC, since at higher temperature the fruit texture was very dry and corky. The thickest epidermis of the persimmons (3 to 5 mm) was obtained when dried at 45ºC.